PHYTOCHEMICAL AND PHARMACOLOGICAL SCREENING OF MALLOTUS PHILIPPENSIS AGAINST CCL4- AND ATT-INDUCED HEPATOTOXICITY IN RATS - T, MUTHURAMU; RAHMAN, MUJEEB UR; MENGESHA YESSU, ABDUROHMAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Mallotus philippensis (Mp) is locally known as kamala and is a large woody multipurpose medicinal tree belonging to the family of Euphorbiaceae. Mp possess a wide variety of activities such as skin problem, bronchitis, antifungal, worm infestation (tapeworm) eye disease, cancer, diabetes, and diarrhea. Hence, the present study was intended to evaluate methanolic fruits extract of Mp for hepatoprotective activities. Methods: The hepatoprotective activity was studied by CCl4 at the dose of 1 ml/kg of body weight in liquid olive oil in the ratio of 1:1 and ATT (isoniazid − 7.5 mg/kg, rifampicin − 10 mg/kg, and pyrazinamide − 35 mg/kg b.w.) induced models. Acute toxicity study and preliminary phytochemical screening were also studied to evaluate the toxicity. Results: No toxicity profile was observed in rats after oral administration of the methanolic fruits extract at the dose of 2 g/kg body weight. The different dose of 300 mg/kg and 500 mg/kg administered with the extract of Mp. There was a significant (p<0.001) reduction in biochemical parameters with respect to control. Phytochemical screening of the fruits extract revealed the presence of tannins, alkaloids, flavonoids and saponins, and terpenoids. Conclusion: It can be concluded that the hepatoprotective activity elucidated by Mallotus philippensis could be mainly due to the presences of high-value class of compound like the phenolic group as the major content in the plant.